THE EFFECTS OF INTERACTIVE GAMES ON THE LEARNING OF ENGLISH FOR THE PRIMARY SCHOOLS - Solijonova Gulshanoy; To'lqinova Durdona; Gaforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This research was developed due to the deficiency in the communication in the English language in students of sixth year of basic education "Eugenio EspejoDiez De Agosto" school, in Guaytacama parish, That is the reason why it has been established the importance of using interactive games to enhance the English teaching-learning process, at the same time to turn the environment into the funniest classes, reaching an interaction between teacher and students in an easy way. It will permit to exchange knowledge and will avoid boredom into the classroom. Therefore, the most important point of this research was to contribute qwith a didactic guide based on interactive games in order that students can apply their knowledge acquired with the objective to improve communicative skills of English language and catch the student´s attention. The students also have the opportunity to engage in a collaborative and interactive class setting. This research was conducted through descriptive method which was used to obtain important information to develop the proposal which will be a reference for students and teachers in the English field to develop the English learning and integrate the knowledge.( Author:Almache Alencastro Susana Del Carmen. AGOSTO 2015”)